Extraction and fractionation of Malaysian seaweed possessing anti-bacteria activity - Tope, Asiyanbi-Hammed Tawakalit (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
With increasing in emergence of resistance pathogenic microorganisms to majority of antibiotics, there is an urgent and continuous need for exploring and developing cheaper and effective plant based drugs with better bioactive potential and least side effects. Bioactive extracts from four species of brown seaweeds (Sargassum plagyophillum, Sargassum flavellum, Padina australis and Sargassum binderi) of Malaysia origin were tested in vitro for their anti-microbial activities against gram positive bacteria (Bacillus subtilis and Staphylococcus aureus) and gram negative bacteria (Pseudomonas aeruginosa and Escherichia coli). Four solvents (methanol, acetone, ethyl acetate and chloroform) were used during the preliminary screening stage to obtain crude extracts. None of the crude extracts displayed antimicrobial activity against the gram negative bacteria while the gram positive bacteria were inhibited. Methanol extract of S. plagyophillum was the best in terms of yield (4.72%) and antimicrobial activity with inhibition zone of 12 mm against B. subtilis. Conditions of extraction (agitation speed, extraction time and temperature) were optimized for methanol extract using Central Composite Design in Response Surface Methodology with yield and inhibition zone as responses. The optimum temperature, agitation speed and extraction time were 420C, 214 rpm and 16 hrs respectively which gave 3.65% yield and 14 mm inhibition zone against. Also, 99.65 and 96.43% of accuracy for yield and inhibition zone was achieved during validation study. Methanolic extract obtained using optimum conditions, was partitioned using solvents (hexane, diethyl ether, chloroform and ethyl acetate) of different polarity. Chloroform fraction gave highest inhibition zone of 17 mm against B. subtilis. Hence, the result from this work showed that S. plagyophillum has the potential for production of antimicrobial extract.